Embedded operating system and industrial applications: a review - Yew Ho Hee; Mohamad Khairi Ishak; Mohd Shahrimie Mohd Asaari; Mohamad Tarmizi Abu Seman (Institute of Advanced Engineering and Science, 2021)
The complexity of an embedded system is directly proportional to the requirements of industrial applications. Various embedded operating system (OS) approaches had been built to fulfil the requirements. This review aims to systematically address the similarities and differences of the embedded OS solutions and analyse the factors that will influence decision-making when choosing what solution to use in the applications. This paper reviews three standard solutions; super loop, cooperative, and real-time operating system (RTOS). These are commonly used in industrial applications. By grouping the tasks in the foreground and background execution region, the concept and working principle of each of them are reviewed. The unique feature of RTOS in the context of task switching was used to define the deterministic characteristic of meeting the deadlines. The importance and performance of this characteristic is addressed and compared among various solutions in this paper. Subsequently, this paper reviewed the internet of things (IoT) requirements, automotive, medical and consumer electronics industry. The influential factors on choosing the right embedded OS to be used are extracted based on the requirements. They are reviewed in the perspective of memory footprint, regulated standards, cost-effectiveness, time effectiveness, and scalability.